The relationship between syncope, depression and anti-depressant use in older adults - CUNNINGHAM, CONAL; KENNY, ROSE (My University, 2014)
The authors aim to examine the rates of depression in older patients reporting syncope and the effect of anti–depressants (ADs) on the rates of syncope. This study demonstrates an increased risk of syncope in patients with depression, with higher rates of syncope reported with increasing severity of depression. Treatment with TCAs increases both the risk and frequency of syncope in the community. Depression is a potentially modifiable risk factor for syncope but treatment options need to be tailored in the older patient population. Methods Epidemiological, point-prevalence study. Data came from the Irish Longitudinal Study on Ageing, which includes 8,175 adults aged 50 and older, living in the community in Ireland. The Centre for Epidemiological Studies Depression scale was used to assess levels of depression. Multinomial regression was used to analyse the data with a P-value of <0.05 determining significance. Results 7,993 participants aged 50 and older were included, and of these 349 reported at least one syncopal episode in the last year. Prevalence of syncope was 4.4%. After controlling for participant characteristics and general health, those with severe depression had a greater risk of single and multiple syncopal events (relative risk ratios [RRR]: 2.78 and 2.84, respectively, P < 0.050) and participants treated with tricyclic anti-depressants (TCAs) were also at greater risk for single and multiple syncopal episode in the last year (RRR: 2.31, P = 0.062; RRR: 2.95, P < 0.05).
PUBLISHED
Keywords: Depression; Ageing; Neuroscience; Age related diseases; Epidemiology; Public health